Anthropometric measurements of the pediatric hip using CT-based simulated anteroposterior radiographs of the pelvis - Darwich, Ali; Bdeir, Mohamad; Janssen, Sonja; Schönberg, Stefan; Gravius, Sascha; Jawhar, Ahmed; Faymonville, Christoph (Journal of pediatric orthopaedics, 2022)
Normal anatomical variants and pathological deformities of the pediatric hip can only be differentiated after a prior definition of normal ranges for anthropometric parameters with increasing age. Aim of the present study was to provide reliable reference values of the pediatric hip morphometry, using computed tomography (CT)-based rotation-corrected summation images of the pelvis that simulate the widely available plain radiograph-based measurements, but offer the higher precision of the CT technique. This retrospective study included 85 patients (170 hips) under 15 years of age (0-15). The measured anthropometric parameters included femur head extrusion index, lateral center-edge angle, acetabular inclination, Tönnis angle, and femoral neck-shaft angle. Mean values, range, SD, P values, intra-rater, and inter-rater reliability were calculated. All measurements correlated with age. None of the measurements correlated with gender or side. Rapid growth phases were noted in all measurements at the age of 12 (14 in males and 11 in females). The inter-rater and intra-rater reliability was high (range inter/intraclass correlation coefficient 0.926-0.998 Cronbach’s alpha 0.986-0.998). The present work provides age- and gender-related normative values of the classically used hip measurements as well as growth phases describing pediatric hip morphology in a broad age range. A discrepancy was noted between the values measured in the current study and the classical X-ray-based reference values in the literature especially for the Tönnis angle and LCEA values. This suggests that the rotation and inclination correction in the CT-based techniques might have the advantage of compensating for a possible overestimation in the conventional X-ray-based methods.